Mechanical load and muscular expenditure in alpine skiracing - Spitzenpfeil, P.; Huber, A.; Waibel, K. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
High external forces acting in alpine ski racing have been published in several studies (Babiel et al. 1997, Mueller et al. 2002). As a consequence alpine skiing athletes spend great efforts on increasing their muscular strength in conditioning training accompanied by different methods of performance diagnostics (Mueller et al. 2002). The presented study tries to compare individually the muscular abilities in lab with the demand on strength during competitive skiing